KONDISI UDANG DAN AIR PEMELIHARAAN SEBELUM MUNCUL PENYAKIT EHP DI UDANG TAMBAK TRADISIONAL - Hamzah Hamzah; Aswar Aswar; Supito Supito (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2021)
Shrimp cultivation in Indonesia is still a lot that implements the traditional shrimp farming system. Traditional shrimp ponds often experience death due to infection with various pathogens, and one of these diseases is EHP or called white peces disease (WFD) because the shrimp droppings are white and floating on the surface of the pond water. So far, shrimp diseases caused by EHP can only be anticipated with preventive measures including selection of superior seeds, increasing shrimp immunity and good aquaculture management. Therefore, it is very necessary to have a prevention effort by carrying out early warning and monitoring of the presence of the disease during the shrimp farming period. Until now, there is still lack of information regarding the description of environmental conditions and shrimp conditions before cases of EHP infection occurred in traditional pond shrimp. Presence of initial information is very important for cultivators in determining the steps to be taken so as not to experience large losses. Therefore, it is important to carry out this research or engineering activity to get a picture of the condition of shrimp and the environment of traditional ponds before EHP infection is detected. The results obtained showed that cases of EHP infection in vannamei shrimp in traditional ponds were characterized by a decrease in the uniformity of shrimp weight to only 20%. There was an increase in cases of filamentous bacterial infection by up to 50%, the temperature and pH of pond water continued to fall along with the length of maintenance